2024
DOI: 10.1039/d4gc00076e
|View full text |Cite
|
Sign up to set email alerts
|

Sequential extraction and separation of soluble humins from fructose conversion for structural and evolutional understanding

Hui Li,
Yexin Hu,
Ping Hu
et al.

Abstract: Understanding the evolution, structure, and separation of humins (i.e., carbonaceous polymeric side-products) during the acid-catalyzed conversion of fructose, especially at high substrate loading, is of crucial importance for future inhibition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They clearly explained the extraction and analysis results of humus, making important contributions to the study of these substances. The main focus of this study is to elucidate the reaction conditions and the two-step process of one pot and two steps in series. , At elevated temperatures, especially exceeding 150 °C, DMSO will undergo excessive decomposition into substances such as dimethyl sulfur and dimethyl thiophenol under the existing hydrogen peroxide. These substances will cause the solution to exhibit a cloudy color and emit irritating and unpleasant gases.…”
Section: Resultsmentioning
confidence: 99%
“…They clearly explained the extraction and analysis results of humus, making important contributions to the study of these substances. The main focus of this study is to elucidate the reaction conditions and the two-step process of one pot and two steps in series. , At elevated temperatures, especially exceeding 150 °C, DMSO will undergo excessive decomposition into substances such as dimethyl sulfur and dimethyl thiophenol under the existing hydrogen peroxide. These substances will cause the solution to exhibit a cloudy color and emit irritating and unpleasant gases.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sharp increase of 100 – TCB from 11.6 to 27.5% with increasing water content from 0 to 2.0 vol % revealed the aggravation of humin formation via the etherification–dehydration–condensation path. However, a negligible effect was observed on the degradative–condensation path to humins in the presence of water because the concentration effect of the substrate was thought to play a crucial role in inhibiting such humins formation …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1a, 94.8% of fructose was converted in EtOH, wherein EMF and EL were detected as the main products with a total yield of 58.1 mol %, whereas HMF (22.3 mol %), EF (10.5 mol %), and a trace amount of FF (0.5 mol %) were detected as the side-products. Our previous work showed that the stoichiometric excess formation of EF relative to EL revealed the occurrence of degradative−condensation of fructose, HMF, and/or EMF to humins, 29 wherein the corresponding carbon loss could be evaluated by the difference between the theoretical carbon balance (TCB) and actual carbon balance (ACB) (i.e., TCB − ACB). Moreover, the etherification−dehydration−condensation of fructose to humins also occurs under a high-substrate concentration condition, wherein the corresponding carbon loss could be calculated using 100 − TCB.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations